2013
DOI: 10.1039/c3dt51339d
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in metal–carbon bond protonolysis in p-tolyl- (or methyl)-cycloplatinated(ii) complexes: kinetics and mechanism of the uncatalyzed isomerization of the resulting Pt(ii) products

Abstract: Reaction of each of the known starting complexes [PtR(C^N)(SMe2)], 1, in which R = Me or p-MeC6H4 and C^N is either ppy (deprotonated 2-phenylpyridine) or bhq (deprotonated benzo[h]quinoline), with one equivalent of CF3CO2H, gave the complexes [Pt(C^N)(CF3CO2)(SMe2)], 3 (C^N = ppy, 3a; bhq, 3b). The bis-chelate complexes [Pt(C^N)(P^P)](CF3CO2), 4, were obtained by reaction of complexes 3 with one equivalent of either of the P^P bisphosphine reagents, dppf = 1,1'-bis(diphenylphosphino)ferrocene or dppe = bis(di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
4
38
0
Order By: Relevance
“…This is the opposite of what has been observed for platinum(II). 135,136 For the platinum complex Pt(N-N)MePh 78, Bercaw et al observed mainly protolytic cleavage of the sp 3 -C of the methyl group, rather than the sp 2 -C of the phenyl (Scheme 3.3). If the gold(III) complex 77-BF 4 in dichloromethane-d 2 was allowed to warm to room temperature, it decomposed to ethane and metallic gold as well as 2-(ptolyl)pyridinium (Scheme 3.2).…”
Section: Reactivity Towards Acidsmentioning
confidence: 99%
“…This is the opposite of what has been observed for platinum(II). 135,136 For the platinum complex Pt(N-N)MePh 78, Bercaw et al observed mainly protolytic cleavage of the sp 3 -C of the methyl group, rather than the sp 2 -C of the phenyl (Scheme 3.3). If the gold(III) complex 77-BF 4 in dichloromethane-d 2 was allowed to warm to room temperature, it decomposed to ethane and metallic gold as well as 2-(ptolyl)pyridinium (Scheme 3.2).…”
Section: Reactivity Towards Acidsmentioning
confidence: 99%
“…The synthesis routes for these complexes are shown in Scheme . Complexes [Pt (bhq)(Me)(SMe 2 )], 1 , and [Pt (bhq)(CF 3 COO)(SMe 2 )], 2 , where bhq = deprotonated 7,8‐benzo[h]quinoline, were prepared as reported in the literature. All the new complexes have shown to be stable powders at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The reagents SMe 2 , trifluoroacetic acid (CF 3 COOH), and NaN 3 and the ligands PPh 3 , PPh 2 Me, dppm, dppe, and dppa were purchased from commercial resources. Complexes [Pt (bhq)(Me)(SMe 2 )], 1 , and [Pt (bhq)(CF 3 COO)(SMe 2 )], 2 , were prepared as reported in the literature. The 1 H NMR labeling for the cyclometalated moiety has been embedded in Scheme .…”
Section: Discussionmentioning
confidence: 99%
“…In this complex the dppf ligand adopts an ''open bridge'' conformation. 2,[5][6][7][8][9][10] However, when complex A was treated with one equivalent of the dppf ligand the PtNbipyO-H bond easily dissociated, and the mononuclear complex [PtMe(κ 1 C-bipyO-H)(dppf)], 2, was formed. This bond breaking is related to the potent chelating ability of dppf ligand due to its large P^P bite angle.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…1,2,4 The dppf is a biphosphine ligand and can adopts numerous coordination modes in complexes of a range of transition metals. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These dppf complexes have been utilized in several area such as catalysis, materials science, electrochemistry, and biology. 1,2,7,9,10,[19][20][21] On the other hand, the chemistry of cyclometalated complexes is of great interest because of their use in a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%